Full mouth rehabilitation of a patient with mandibular implant screw retained Fp-3 prosthesis opposing maxillary acrylic removable over-denture - Ashish R Jain; Deepak Nallaswamy; Padma Ariga; Jacob Mathew Philip (Wolters Kluwer Medknow Publications, 2013)
A hybrid denture is one that is fabricated over a metal framework and retained by screws threaded into the implant abutments. The anterior part of a mandibular hybrid denture is fixed on implants while the posterior part of the denture is extended and cantilevered from implants. This article presents the fabrication of a maxillary over-denture opposing mandibular implant retained hybrid prosthesis. A total of four implants were placed in the mandibular arch. Castable abutments were used to produce the optimal angulations. Framework was waxed, cast recovered, and the fit was refined until the framework seated passively on the master cast. The mandibular denture teeth were waxed to the hybrid framework, and a final wax try-in was performed to verify and correct maxillomandibular relations before processing. The prosthesis was inserted after verification of occlusion, retention, and stability. The rehabilitation of edentulous patients with hybrid dentures has been observed to achieve greater masticatory function and psychological satisfaction than with conventional over-dentures. Producing a passive-fitting substructure for a fixed removable screw retained hybrid prosthesis is arguably one of the most technically complex tasks in implant dentistry. The technique presented may not initially produce a perfectly passive framework, but use of disclosing media and adjusting the internal aspect of the casting can result in non-binding, fully seated prostheses.